Efektivitas Pelaksanaan Program Bantuan Benih Jagung Hibrida di Kecamatan Nagreg Kabupaten Bandung - Gunawan, Agus; Wulandari, Eliana; Suminartika, Eti (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2022)
Corn is a food-crop commodity that has a strategic role in national development. Achievement of corn productivity is still relatively low. Under these conditions, the government has distributed assistance in the form of hybrid corn seeds of the BISI variety intending to increase productivity. This research was conducted in Nagreg District, Bandung Regency. This study aimed to analyze the effectiveness of the implementation of the hybrid corn seed assistance program and identify the necessary actions. This research employed a survey method. The research sample was taken using proportionate stratified random sampling on a sample of 73 farmers spread over 32 farmer groups. Data analysis used gap analysis to analyze the effectiveness of the program and Importance Performance Analysis (IPA) to identify the necessary actions. The results of the study indicated that the implementation of the hybrid corn seed assistance program has not been fully effective in increasing the productivity of corn farming. Suggestions for the government that further assistance programs to pay attention to the varieties of seeds distributed have proven productivity, to pay attention to the implementation schedule so that seed distribution can be on time, and to improve supervision in the field and apply strict sanctions for a delay in seed distribution.Â Jagung merupakan komoditas tanaman pangan yang memiliki peran strategis dalam pembangunan nasional. Pencapaian produktivitas jagung masih relatif rendah. Dengan kondisi tersebut pemerintah telah menyalurkan bantuan berupa benih jagung hibrida varietas BISI dengan tujuan meningkatkan produktivitas. Penelitian ini dilakukan di Kecamatan Nagreg Kabupaten Bandung. Penelitian ini bertujuan untuk menganalisis efektivitas pelaksanaan program bantuan benih jagung hibrida dan mengidentifikasi tindakan yang diperlukan. Penelitian ini menggunakan metode survey. Pengambilan sampel penelitian menggunakan proportionate stratified random sampling pada sampel sebanyak 73 petani yang tersebar di 32 kelompok tani. Analisis data menggunakan analisis gap untuk menganalisis efektivitas program dan Importance-Performance Analysis (IPA) untuk identifikasi tindakan yang diperlukan. Hasil dari penelitian menunjukkan bahwa pelaksanaan program bantuan benih jagung hibrida belum Â sepenuhnya efektif meningkatkan produktivitas usaha tani jagung. Saran bagi pemerintah agar program bantuan selanjutnya memperhatikan varietas benih yang disalurkan sudah teruji produktivitasnya, memperhatikan time schedule pelaksanaan sehingga penyaluran benih bisa tepat waktu, dan meningkatkan pengawasan di lapangan serta menerapkan sanksi yang tegas jika terjadi keterlambatan penyaluran benih.